EKSPLORASI ETNOMATEMATIKA PADA OLEH-OLEH MAKANAN KHAS KOTA MADIUN - Dewi, Lenny Puspita; Pradana, Yan Aditya; Iswari, Dian Ardifah; Shobri, Muhammad Qolbi; Ishartono, Naufal; Pratiwi, Citra Kusuma (De Fermat : Jurnal Pendidikan Matematika, 2026)
Negative perceptions of mathematics persist, largely due to its abstract nature and the limited use of concrete examples in instruction. Integrating cultural elements into learning can provide an alternative approach to support a more contextualized understanding of mathematical concepts. Ethnomathematics serves as a bridge between culture and mathematics within the learning process. This study aims to explore ethnomathematical concepts embedded in traditional food products of Madiun City, namely brem, bluder, and lempeng. A qualitative approach with an ethnographic method was employed. Data were collected through observation, direct measurement of the research objects, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results of the study indicate that various mathematical concepts are present in the production and packaging processes of traditional foods. In brem, concepts of the rectangular prism, measurement, and volume were identified. In bluder, concepts of the truncated square pyramid, base area, height, and volume were identified. Meanwhile, in lempeng, the concepts of the rectangular plane figure, the rectangular prism, area, volume, and the size ratio between raw and cooked lempeng of 1:2 were found. These mathematical concepts appear implicitly in the cultural activities of the community, particularly in the production and packaging processes of traditional foods.